Asia's role in the global economic architecture - Masahiro Kawai; Peter A. Petri (Asian Development Bank Institute (ADBI), 2010)
The global economic and financial landscape has been transformed over the past decade by the growing economic size and financial power of emerging economies. The new G20 summit process, which includes the largest emerging economies, has established high-level international policy cooperation in this new setting. This paper argues that effective global economic governance will also require changes in key global organizations - such as the International Monetary Fund, World Bank, World Trade Organization, and the Financial Stability Board - and closer collaboration between global and regional organizations. We suggest that federalism be introduced on a global scale by creating hierarchies of global and regional organizations with overlapping ownership structures in various functional areas (as is already the case with the World Bank and regional development banks in the area of development finance). Asia could contribute to this transformation by building effective institutions to promote macroeconomic and financial stability and deepen regional trade and investment integration.
Keywords: F02; F13; F33; F55; O59; 330; Weltwirtschaftsordnung; Global Governance; Internationale Wirtschaftsorganisation; Asien; Welt